Meal timing and obesity: interactions with macronutrient intake and chronotype - Xiao, Qian; Garaulet, Marta; Scheer, Frank A J L (International Journal of Obesity, 2019)
Timing of dietary intake may play a role in obesity. However, previous studies produced mixed findings possibly due to inconsistent approaches to characterize meal timing and not taking into account chronotype and macronutrients. To address the aforementioned limitations, we have defined meal timing relative to sleep/wake timing, investigated the relationship between meal timing and body mass index (BMI) dependent on chronotype, and examined the associations. BMI, chronotype, and dietary intakes were measured in 872 middle-to-older-aged adults by six 24-h dietary recalls in 1 year. We defined four time windows of intake relative to sleep timing: morning (within 2 h after getting out of bed), night (within 2 h before bedtime), and two midday periods in between (split by the midpoint of the waking period). A higher percent of total daily energy intake consumed during the morning window was associated with lower odds of being overweight or obese (odds ratio (95% confidence intervals), 0.53 (0.31, 0.89)). This association was stronger in people with an earlier chronotype (0.32 (0.16, 0.66)). A higher percent of total daily energy intake consumed during the night window was associated with higher odds of being overweight or obese (1.82 (1.07, 3.08)), particularly in people with a later chronotype (4.94 (1.61, 15.14)). These associations were stronger for the intakes of carbohydrates and protein than for fat intake. Our study suggests that higher dietary consumption after waking up and lower consumption close to bedtime associate with lower BMI, but the relationship differs by chronotype. Furthermore, the data demonstrate a clear relationship between the timing of carbohydrate and protein intake and obesity. Our findings highlight the importance of considering timing of intake relative to sleep timing when studying the associations of meal timing with obesity and metabolic health.